(untitled) (Bioagro, 2022)
The Portoviejo valley in the Manabi province, Ecuador, is an important ‘Sutil’ lime (Citrus aurantifolia Swingle) producer, but since the water resources in the region are of vital importance, a good management of the irrigation is needed. The objective of this research was to know the physiological response of the plant expressed in terms of gas exchange and fluorescence, under different levels of irrigation. The study zone is located at Maconta site, 40 masl, in an orchard with 15 year old plants grafted on rootstock ‘Cleopatra’, planted at 6 x 6 m. The following irrigation treatments were tested, according to the atmospheric demand: 0.3ET0, 0.5ET0, 0.7ET0, 0.9ET0, and a control (farmer’s irrigation). A randomized complete block design with five treatments and six replications was established. Significant differences (P≤0,05) were found among treatments measured in the dry season, where the photosynthesis rate (A) was higher in the control treatment, decreasing in those treatments with water restrictions (0,3ET0) or excess (0,9ET0) in the soil. Similar behavior was observed in stomatal conductance (gs) and transpiration (T); the increase or decrease of A, would be associated with T and gs. The water use efficiency (WUE) was higher in the treatment of 0,5ET0 than in the rest of treatments, suggesting that the increase in this variable would be due to a good equilibrium of the Ci/Ca, ratio, avoiding water loss and still maintaining active physiological processes. Low values of the Fv/Fm ratio existed in conditions of excess moisture. The performance of gs in both periods leads to deduce the rapid adaptation of the crop to different levels of soil moisture.